Impact of integrated weed management on weed biomass, growth and yield of maize (Zea mays L.) in Kunar, Afghanistan - Azizullah Khalili; Shiva Dhar; Anchal Dass (Annals of Agricultural Research, 2023)
Weeds are the major pest of maize and adversely affect growth and yield of crop. A field experiment was conducted during spring season of 2018 at Research Farm of Sayed Jamaluddin Afghani University (SJAU), Kunar, Afghanistan to assess the impact of integrated weed control methods on weed biomass and performance of maize crop. The experiment consisted of seven treatments, viz., T1 Unweeded; T2 Weed free; T3 Two times hand weeding at 20 and 50 DAS; T4 atrazine @ 0.75 kg a.i. ha-1 as pre-emergence; T5 atrazine @ 1 kg a.i. ha-1 as pre-emergence; T6 atrazine @ 0.75 kg a.i. ha-1as pre-emergence with a hand weeding at 50 DAS and T7 atrazine @ 1 kg a.i. ha-1as pre-emergence with a hand weeding at 50 DAS and laid out in randomized block design (RBD) with three replications. The results indicated that there were many weeds species observed in the field of experiment, but the major weed species were Cyperusrotundus, Sorghum halepense,Cynodondactylon, Convolvulus arvensis, Chenopodium album, Trianthema portulacastrum, Portulacaoleraceae, Parthenium hysterophorus and Setariaviridis. The result showed that, the most effective treatment among other treatment in controlling weed population and increased the growth and grains yield of maize were weed free and atrazine @ 1 kg a.i. ha-1 as pre-emergence with a hand weeding at 50 DAS. These approaches of weed management significantly controlled weed and improved the yield and yield component of maize in the experiment. Thus, it was concluded that, atrazine @ 1 kg a.i. ha-1 as pre-emergence with a hand weeding at 50 DAS is more effective in term of weed control and yield of maize as compared to other treatments.